Developmental delay and related factors - Soleimani, Farin; Sajedi, Firozeh; Amir Ali Akbari, Sedigheh (Advances in Nursing & Midwifery, 2015)
Background & objective: The survival rates of high-risk infant have been improved as a result of advances in medical knowledge, but future development of these children is becoming a matter of concern. After infection and trauma, developmental and behavioral problems are the most common problems in pediatrics. A range of factors are involved in behavior and development problems. Given the importance and prevalence of developmental disorders, the lack of detailed information on risk factors, this article aims to explore some factors associated with developmental delay in children. Method and Material : This review was performed by searching PubMed, Ovid, SID, Scopus, Magiran and Science Direct databases using following key words: Child Development, Socioeconomic statue, Violence, Social support, Psychological factors, Unhealthy behavior, Social Determinants. A total of 55 article were included in this review . Results: The main causes of developmental disabilities remain unknown. Development of children affected by prenatal factors, psychological, social and biological factors, genetic, environmental factors and is dynamic interaction Biological and Acquired factors. Key words: Developmental delay- Risk factors - Socioeconomic risk factors -Biological risk Factors-environmental risk factors